Sri Lanka in the modern age : a history of contested identities - Wickramasinghe, Nira. (London : C. Hurst & Co. ; New Delhi : Distributed in South Asia by Foundation Books, 2006)
On the ethnic relations and politics in post 1978 Sri Lanka.
Includes bibliographical references (p. 335-351) and index.
Keywords: Tamil (Indic people) -- Sri Lanka -- Ethnic identity; Sinhalese (Sri Lankan people) -- Ethnic identity; Sri Lanka -- Ethnic relations -- Political aspects; Sri Lanka -- Politics and government -- 1978-